(untitled) (Semiárida, 2020)
Modifications in the initial growth of the wheat produced by changes in seedling rates and nitrogen availability, measured through the dry matter production, the number of tillers, the number and size of Leaves and the total nitrogen in the air dry matter. were determined in this trial. Densities equivalent to 670, 1.340 and 2.009 plants per square meter, with addition of ammonium nitrate reaching the levels of 50, 100 and 150 kg of nitrogen per hectare, were compared in pots. Increasing the seeding rate reduced dry matter production per plant but increased total production per unit area. The addition of nitrogen produced significant increments in the dry matter production per plant as well as in the pots, so that kg/ha of added nitrogen would counter balance the variation of production caused by the modification in the seeding density of 700 plants per square meter. The production oy tillers and leaves decreased when the seeding rate increased and was higher with the increment of the fertilization rate. Most of fertilizer was absorbed during the first 30 days. Nitrogen content varied inversely with density.